A case of primary aldosteronism caused by unilateral multiple adrenocortical micronodules presenting as muscle cramps at rest: The importance of functional histopathology for identifying a culprit lesion. Issue 4 (5th March 2017) - Ito, Atsushi; Yamazaki, Yuto; Sasano, Hironobu; Matsubara, Daisuke; Fukushima, Noriyoshi; Tamba, Mio; Tabata, Kenichi; Ashizawa, Kentaro; Takei, Akihito; Koizumi, Masaru; Sakuma, Yasunaru; Sata, Naohiro; et al.
Abstract : Unilateral multiple adrenocortical micronodules (UMNs) constitute a rare subset of primary aldosteronism (PA) characterized by the hypersecretion of aldosterone derived from multiple small nodules in the zona glomerulosa of the unilateral adrenal grand. This case study describes a 49‐year‐old man with PA and UMNs who presented with muscle cramps at rest due to hypokalemia. The patient had a 6‐year history of hypertension treated with antihypertensive drugs. Imaging studies revealed bilateral adrenal nodules as large as 5 mm. Adrenal venous sampling confirmed unilateral PA; therefore, the patient underwent the removal of the affected adrenal gland. Macroscopically, the removed adrenal gland exhibited irregular adrenocortical thickening accompanied by ill‐defined, adrenocortical macronodules as large as 6 mm. The zona glomerulosa was histologically hyperplastic. However, an immunohistochemistry test of the steroidogenic enzymes revealed that these macronodules and the hyperplastic glomerular layer tested negative for CYB11B2. Moreover, we observed adrenocortical micronodules as large as 0.5 mm that tested immunohistochemically positive for CYP11B2 and HSD3B2 but negative for CYP17A1 and CYP11B1. Thus, UMNs were diagnosed. This case instructively indicates that a grossly or histologically detectable nodular lesion is not necessarily a culprit lesion for PA. Therefore, functional histopathology is indispensable for the correct subclassification of PA.